The Conception of Tasawuf Morals in The Learning Process of Islamic Religious Education - Taufan; Muhammad Aminullah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This article aims to find out about the study of the koran regarding Sufism's morals, to find out about the aims and functions of Sufism's morals in education and to provide various explanations regarding the implementation of Sufism's moral education in Islamic religious education learning. So the results of the research conclude that the concept of morals-Sufism in learning Islamic education provides a study of approaches to behavior and feelings of doing good, all based on the manifestation of piety and goodness, for the sake of human progress in life. Thus, moral-sufism education in the realm of Islamic education learning provides the formation of spiritual and personality morals, as well as Islamic ethics then provides aspects of calm, peace and intuitive happiness but is then developed not only for individuals but also in the form of social piety in order to fulfill hablum minallah wa hablum minannas, which practically applies the morals of Sufism in the realm of Islamic education learning, namely: First, Habituation method (Ta'widiyah) can be interpreted as a way that can be used to familiarize students with thinking, behaving and acting in accordance with the guidance of Islamic teachings. Second, method it's okay (exemplary) which provides an example of good deeds so that other humans can follow in goodness. Third, method mau'izha a method or effort to give advice about the truth by reminding, reprimanding, inviting and directing accompanied by an explanation of the good and bad of something. Fourth, method tsawab and rewards. should be motivated in such a way with gifts or rewards.